The nature of the symbolism in Conrad's Nostromo : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Baigent, H. G (Massey University, 1978)
Conrad's writing is frequently described as symbolic, but few critics agree on the application of this term. There are those critics who identify Conrad with the French Symbolist poets and discuss his works only with reference to the essence, the ideal and the general, ignoring the literal, the experience level, and avoiding all mention of the narrative in which the symbolism is based. And there are those who pick out particulars from the narrative and match them up with a series of one-to-one correspondences, thus missing the general and universal implications. Both of these interpretations, and a good many analyses in between, do Conrad a serious injustice. His work is first of all narrative—his novels are, among other things, rollicking good adventure stories—but beyond the literal and the particular it also contains a wealth of suggestion and association that defies rigid interpretation. Above all there is an underlying ambivalence, a sense of the relativity of things: assigned values are subject to sudden inversion and nothing can be accepted as ultimate. To attempt to categorize such art is to restrict the free play of the imagination which goes beyond the "temporary formulas" of literary criticism, as Conrad himself calls them. To attempt to interpret the symbolism systematically not only extracts the symbols from the narrative on which they depend for their scope and force but introduces an element of the finite that is inappropriate in Conrad. This study is a discussion of the symbolic nature of Nostromo in an attempt to rediscover the novel as a whole, to, as it were, put the trees back in the wood. The theory of symbolism is discussed briefly in order to cancel any restrictive critical categorization and in particular to disentangle Conrad from too close an association with the French Symbolist poets. A number of interpretations of Nostromo are looked at in detail to demonstrate how attempts at definitive criticism can distort and restrict as much as they can elucidate. Finally there is a focus on some aspects of the novel as an indication of the intricate way in which the literal and the symbolic are interwoven and interdependent: an appreciation of the texture of the surface and of the infinity of its translucence.
Keywords: Symbolism in literature; Conrad, Joseph, 1857-1924